A Modern View of the System of Crime Prevention Subjects - Lytvynov, Oleksii; Kliuiev, Oleksandr (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2022)
The article carries out a system-structural analysis of the crime prevention subjects as a basic criminological category. The main scientific approaches to the definition of crime prevention subjects have been defined and analyzed: as a collection of crime prevention subjects and as a corresponding system of these subjects. The expediency of subjects’ consideration operating in the sphere of crime prevention as a socially determined hierarchical system has been argued. It has been proved that systematic approach to solving this issue allows to determine the place and role of the specified subjects in the general structure of crime prevention, to outline their functional connections, to overcome the possible duplication of performed functions, and if it is necessary to strengthen the influence on a certain segment of criminogenic factors. The role of citizens as autonomous subjects of crime prevention has been analyzed. The expediency of including citizens in the system of crime prevention subjects through the category of citizenship, which in the analyzed aspect is proposed to be understood as the internal conscientious attitude of a person to the fulfillment of their civic duty in the field of crime prevention, has been determined. The article develops the author’s understanding of the concepts of the subject of crime prevention and the system of crime prevention subjects.
Keywords: crime prevention; the subject of crime prevention; the system of crime prevention subjects; citizens; civic duty; citizen control